The Influence of Healthcare Services, Nursing Actions, and Communication on Post-Operative Patient Satisfaction at HNGV Hospital, Dili, Timor-Leste - Silva, Sanzina Agus da; Murtiningsih, Murtiningsih (International Journal of Psychology and Health Science, 2025)
This study aims to examine the influence of healthcare services on patient satisfaction after surgery, assess the impact of nursing interventions on postoperative patient satisfaction, evaluate the effect of communication between healthcare providers and patients on postoperative patient satisfaction, and identify the dominant factors influencing postoperative patient satisfaction at Hospital HNGV, Dili, Timor-Leste. The study adopts a systematic approach by conducting a literature search through reputable journal databases such as Google Scholar, Wiley Online Library, and Sage Journal. Inclusion criteria include articles published within the last 10 years. Subsequently, the authors conducted a search and selection of relevant studies for review using the PIOS framework (Population, Intervention, Comparison, Outcome). The findings of this study conclude that effective communication is a key factor in improving the quality of healthcare services. Structured communication interventions were found to reduce family anxiety and increase patient satisfaction, with approximately 70% of patients reporting satisfaction after receiving postoperative services. The study also highlights the importance of continuing education for nurses, with 80% of patients expressing the need for improved nurse training related to postoperative care.